2020
DOI: 10.1002/jmv.25776
|View full text |Cite
|
Sign up to set email alerts
|

Alert for non‐respiratory symptoms of coronavirus disease 2019 patients in epidemic period: A case report of familial cluster with three asymptomatic COVID‐19 patients

Abstract: prevention and management. Here we reported the screening, clinical feathers, and treatment process of a family cluster involving three COVID-19 patients. The discovery of the first asymptomatic carrier in this family cluster depends on the repeated and comprehensive epidemiological investigation by disease control experts. In addition, the combination of multiple detection methods can help clinicians find asymptomatic carriers as early as possible. In conclusion, the prevention and control experience of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 3 publications
(6 reference statements)
1
123
0
7
Order By: Relevance
“…As has occurred in other affected countries elsewhere, there is a risk of local clusters of transmission from imported cases [1,[43][44][45][46]. Precisely, the first case in Bolivia, originated the transmission to other seven cases in two different departments of the country, as the patient travelled to Santa Cruz, Cochabamba, La Paz and Oruro (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As has occurred in other affected countries elsewhere, there is a risk of local clusters of transmission from imported cases [1,[43][44][45][46]. Precisely, the first case in Bolivia, originated the transmission to other seven cases in two different departments of the country, as the patient travelled to Santa Cruz, Cochabamba, La Paz and Oruro (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…1). Close contact with active cases of COVID-19 represents a significant risk for SARS-CoV-2 transmission, even during the asymptomatic or presymptomatic stage, especially for relatives or friends [19,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from single-center reported 4% to 6% cases with SARS-CoV-2 did not develop any symptom during the course of the disease. 5,6 Thus, there is very little probability that the virus-positive asymptomatic individuals will develop symptoms later, the ratio is slightly smaller than that of influenza, which was estimated at 56% to 80%. Recently, a preprint published on medRxiv analyzed the evolving epidemiology before and after nonpharmaceutical interventions put into effect using an SEIR model.…”
Section: How Many Asymptomatic Cases?mentioning
confidence: 99%
“…This is because we don't, as of now, have any reliable estimates of the total number of people infections by this virus. This is due the fact that many SARS-CoV-2 infected individuals are asymptomatic and never get tested Lu et al, 2020;Mizumoto et al, 2020;Lin et al, 2020). The number of people who are infected with SARS-CoV-2 may be notably higher than the actual confirmed cases indicating that the CFR of COVID-19 may be notably less than the estimated rate.…”
Section: Infectivity Mortality and Morbiditymentioning
confidence: 99%